MIDWIFE SUPPORT IN IMPROVING QUALITY GIVING EXCLUSIVE BREASTFEEDING IN BONTOBANGUN VILLAGE - Amin, Andi Nurzakiah; Zulkifli, Andi; Suriah; Jafar, Nurhaedar; Maidin, Alimin; Abdullah, Tahir (International Journal of Psychosocial Rehabilitation, 2020)
Health services especially hospitals or child-friendly health centers in developing countries, especially Indonesia, have not fully implemented exclusive breastfeeding. So that the most possible way to approach services that are in favor of mothers and infants is the midwife in the village. Therefore this study aims to explore the forms of roles perceived and carried out by village midwives in supporting exclusive breastfeeding. The design of this study used descriptive phenomenology by using a taxonomic analysis to explore the extent of midwife support in increasing exclusive breastfeeding. Determination of the research sample using purposive sampling, where in total there were 15 women, consisting of 10 mothers and 5 midwives who participated; 5 of these people have midwifery experience of more than 5 years and their ages range from 23-30 years. Ten nursing mothers aged 16-35 years. Based on the results of in-depth interviews, midwives gave rich statements about their experiences in assisting exclusive breastfeeding to mothers for years. Two main themes were identified, 1) exclusive breastfeeding services and 2) perceptions related to exclusive breastfeeding. During the interview process to the midwife, they stated that during the process of pregnancy from mother to childbirth the assistance process related to exclusive breastfeeding did not run optimally. Midwives repeatedly reflect on the picture of the mother’s failure to provide exclusive breastfeeding without assistance. Some midwives revealed that the absence of a special program would breastfeed and so many tupoksi inhibited the midwife’s assistance to mothers regarding exclusive breastfeeding. Some midwives also revealed that they still recommend giving formula milk to mothers if they experience dif iculties, and they are still working with the formula milk industry that provides profit and non-profit benefits. The conclusion in this research is the lack of midwife service to mother will influence mothers’ perception of exclusive breastfeeding with the proliferation to mothers of ering products and promotion of quality.